Applications of Calcium Oxalate Crystal Microscopy in the Characterization of Baccharis articulata. - RAESKI, P. A. (2023)
Baccharis articulata (Lam.) Pers., popularly known as carqueja, carquejinha or carqueja-doce, is a plant widely used in traditional medicine as a diuretic, digestive and antidiabetic. Due to its similar morphology with other species of the "carqueja group", especially Baccharis pentaptera (Less.) DC., it can be easily confused even by specialists. Thus, this study aimed to characterize micromorphology of the crystals present in B. articulata to show botanical markers that can help differentiate this species from other carquejas. Eleven crystalline morphotypes, including druses, styloids and various shapes of prismatic and sand crystals, were evidenced by scanning electron microscopy. In addition, the elemental chemical composition and the degree of hydration of the crystals were analyzed by EDS and Raman spectroscopy. The results of this study would aid in the authentication of B. articulata and serve as a basis for future studies of other species of Baccharis.